Uso de la técnica de relajación térmica para la medición de calor específico de láminas recubiertas con TiO2 - Gordillo-Delgado, Fernando (Scientia et Technica, 2019)
Specific heat (Cp) is a necessary thermal parameter for describing heat transport phenomena, related to adaptation to temperature changes. For this reason, it is important in the construction, glue, thermal insulator and electronic device industry. In this work, a thermal relaxation system was used to determine the Cp of Ti sheets, coated with S-TiO2 by Plasma Electrolytic Oxidation (EPO). Each sample was placed inside a vacuum chamber that reaches around 10-2 Torr and was heated by the incidence of a laser beam of 450 nm wavelength; an infrared (IR) thermometer was located at the bottom of the sample and the data obtained was sent to a computer using a programmable development card. The validation of the system was done by comparing the results with those reported by other authors for zinc, tungsten, titanium and steel. The Cp of the OEP coated Ti samples, which were obtained using an electrolyte with two concentrations of thiourea (CH4N2S) and with a voltage applied between the electrodes at 2 kHz with useful cycles of 10%, 20%, and 30%, were measured and compared in order to study the influence of growth parameters on the thermal characteristics of the material. The results of the analysis of variance of the data led to find significant differences, with a confidence level of 95%, related to the variation in the concentration of CH4N2S.